Draft Annual Plan 2012-13 Volume-III Scheme Wise details (Financial and Physical) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2012)
Head of Development Wise Details, State Plan 2012-13 (Scheme -Wise Details), Crop Husbandry, Animal Husbandry, Fisheries, Forests, Agriculture Research and Education, Co-operation, Rural Development, Irrigation and Flood Control, Energy, Village and Small Scale Industries, Large and Medium Industries, Mining, Transport, Science, Technology and Environment, Secretariat Economic Services, Tourism, Economic Advice and Statistics, Legal Metrology (Weights and Measures), Civil Supplies.
Planning Department, Government of Andhra Pradesh